THEORETICAL AND METHODOLOGICAL BASES OF TEACHING WRITTEN TRANSLATION - Absamadova Munira Isroilovna (Scholars Digest Publishing, 2023)
To solve the problems set by us in this article, it is required to define and analyze the basic concepts underlying the methods of teaching a foreign language and translation, and on their basis to develop new, additional definitions related to the problematic field of teaching translation to students of the specialty "Translation and translation studies".
Keywords: pedagogy note, module-contextual, systemic, activity-oriented, student-oriented, competence-based approaches, transformation.